(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims at discussing the Ulysses theme in Toni Morrison’s novel Song of Solomon. Song of Solomon is a migratory narrative where Morrison shows her concern for people who migrated from the South to the North. It shows that the main problem these people face is that of their relationship with the past. Symbolically and literally they move away from their origins, but a fruitful relationship can still be maintained with their past heritage only if the people themselves are willing. She presents the male adventure story from a woman’s perspective. Morrison adds another dimension to this theme of Ulysses by concentrating equally on the suffering of his wife and son as well. Morrison, as an Afro-American writer, tries to focus on the cultural heritage of the people of African descent.